The Reform in Evaluation System as a Tool of Quality Improvement in Institute of Engineering - Pahari, Bharat Raj (Journal of the Institute of Engineering, 2014)
The present day notion is such that technology and technical education is treated as backbone of economy. Earlier understanding of education producing wisdom and building elite society has been changed; education is taken as the means of increasing productivity. This has demanded the quality engineering education that produces human resource capable enough to cope the growing need of the market and yield product of consumers' satisfaction. Institute of Engineering has established as an icon of quality engineering education in Nepal is putting its efforts in increasing its quality in the changing context. Though it is continuous process, IOE has applied some corrective measures to attain effective and efficient output in the institution. This paper is an attempt to shed light on the improvements in the evaluation system (examination) of IOE and analysis of the exam results. DOI: http://dx.doi.org/10.3126/jie.v10i1.10872 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 1–13